FAKTOR - FAKTOR YANG MEMPENGARUHI NIAT KETIDAKPATUHAN DALAM MEMBAYAR PAJAK (Studi Empiris Terhadap Wajib Pajak PBB-P2 Kabupaten Sukoharjo) - Winarsih, Endang Sri (MAGISTRA, 2015)
The purpose of this reseach is to determine what the factors that influence non-compliance inpaying taxes. Respondents are used in this reseach is the taxpayer domiciled in Sukoharjo. This reseach usesprimary data with purposive sampling method in the determination of the sample.This reseach uses attitudes, subjective norms, moral obligation, and perceived behavioral control asindependent variables and intentions of non-compliance as the dependent variable. The method of analysis inthis reseach using multiple linear regression analysis with SPSS for Windows 17:00. The results ofthis studyindicatethattogetherattitudes, subjective norms, moral obligation, andperceivedbehavioralcontrolpositive effecton theintentionof non-compliance.Key word: attitude, subjective norm, moral obligation, perceived behavioral control and intention non-compliance.